The Relevance and Application of Structuralist Linguistics in Arabic Language Learning - Rohiqi Rohman; Mualim Wijaya (Jurnal Educatio FKIP UNMA, 2023)
Structuralist theory is one of the important theories in language learning. This theory raises fundamental questions regarding its relevance to language, especially second language. This study aims to describe the view of structuralist theory and its application in Arabic language learning. This research is a conceptual study using descriptive-qualitative method. The results show that some learning models that can be applied based on structuralist views are; 1) repetitive practice of Arabic utterances that can have an impact on students' habituation in speaking Arabic, 2) changing the type of sentence between isim or fi'il, 3) Expansion of meaning exercises in sentences with different patterns, and 4) linking exercises.